Laser systems for time‐resolved experiments at the Pohang Accelerator Laboratory X‐ray Free‐Electron Laser beamlines. (15th April 2019) - Kim, Minseok; Min, Chang-Ki; Eom, Intae
Abstract : The experimental lasers at the PAL‐XFEL beamlines, from the source to the sample position, are described. Abstract : Optical laser systems for ultrafast X‐ray sciences have been established at the Pohang Accelerator Laboratory X‐ray Free‐Electron Laser (PAL‐XFEL) beamlines. Three Ti:sapphire regenerative amplifier systems are synchronized to the XFEL with femtosecond precision, and the low temporal jitter of the PAL‐XFEL results in an experimental time resolution below 150 fs (full width at half‐maximum). A fundamental wave and its harmonics are currently provided for all beamlines, and tunable sources from ultraviolet to near‐infrared are available for one beamline. The position stability of the optical laser extracted from the intensity‐based center of mass at the sample position is less than 3% (r.m.s.) of the spot size.